MALLO: A New Paradigm for Ubiquitous Language Learning - Sukavatee, Pornpimol; Khlaisang, Jintavee (rEFLections, 2023)
One of the greatest advantages of mobile language learning is its ease of access, especially to learners in the 21st century who have the option of selecting any learning content that matches their preferences or language development goals, anywhere and at any time. Mobile-assisted language learning or MALL takes learning beyond the classroom, which imposes spatial and temporal constraints. This study aims to investigate components of language learning with a mobile-assisted design, and develop and evaluate a mobile-assisted English language learning and teaching innovation, namely Mobile-Assisted Language Learning in Open Resources Environment or MALLO for high-school English as a foreign language (EFL) students. MALLO is a research-based application which employs Exploratory Factor Analysis (EFA) in its development to identify significant components. The participants in this study consist of two sample groups: 1,500 high school students from six regions of Thailand to explore the components; and 300 students to examine MALLO users’ satisfaction Both were selected via the stratified sampling method. After that, nine experts evaluated MALLO in terms of its components, its support for English language learning, its functions, and its application for English language learning. The results indicate that MALLO is comprised of four important components: mobile English learning resources, the use of MALL, mobile technology, and portal collective tools. The results also show the satisfaction of learners as users of the MALLO application at high levels with an average of 4.05 to 4.15. In the final stage, the MALLO application was evaluated by nine experts and the results were also in the range of high or very high levels across all aspects, with an average rating of 4.444.72.